The relationship between nasal septal deviation and anatomical variations of the paranasal sinus - Dikici, Oğuzhan; Durgut, Osman (The European Research Journal, 2021)
Objectives: The aim of this study was to determine the relationship between septum deviation and anatomic variations of the paranasal sinus. Methods: A total of 157 (79 males, 78 females) patients between the ages of 17 and 77 years (mean age: 33.7 ± 14.9 years) were included in the study. Using paranasal sinus computed tomography imaging, anatomical variations including nasal septal deviation, Agger nasi cells, Haller cells, Onodi Cells, sphenoid sinus pneumatisation, paradoxical middle turbinates, middle turbinate pneumatisation, maxillary sinus septa,vertical septa in the sphenoid sinus, optic nerve dehiscenceand cribriform plate lamina lateralis height were evaluated. Results: Agger nasi cells were present in 47.1% of cases, Haller cells were seen in 5% of cases and Onodi cells were observed in 23.6% of cases. In 70.1% of cases, one vertical septa in the sphenoid sinus was observed. Maxillary sinus septa was observed in 16.5% of cases. There was a significant negative correlation between the female gender and increased sphenoid sinus pneumatisation (p = 0.035). There was a positive correlation between maxillary sinus septa and the presence of Onodi cells (pright =0.045, pleft = 0.017). There was also a negative correlation between maxillary sinus septa and sphenoid sinus pneumatisation (pright = 0.001, pleft = 0.005). Conclusions: In our study, we found that maxillary sinus septa, Agger nasi, Haller cells, cribriform plate lamina lateralis height, sphenoid sinus septation and Onodi cells were interrelated. We recommend that surgeons evaluate patients with these variations to prevent complications.